2006
DOI: 10.1016/j.jtcvs.2005.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Single crossclamp improves 6-month cognitive outcome in high-risk coronary bypass patients: The effect of reduced aortic manipulation

Abstract: A surgical strategy designed to minimize aortic manipulation can significantly reduce the incidence of cognitive deficits in coronary artery bypass grafting patients compared with traditional techniques. In this series, the results of the reduced aortic manipulation strategy were not significantly different from those in patients having off-pump coronary artery bypass surgery, thus emphasizing surgical technique as the primary cause of brain damage in coronary artery bypass grafting patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 14 publications
0
49
1
4
Order By: Relevance
“…Our results obtained in low-risk CABG are different from Hammon et al 23 who in higher-risk cases observed reduced rates of POCD with the modified single-clamp technique but no reduction in the HITS counts. Our findings are similar to those by Mullges et al 17 who did not find any effect on the rates of POCD due to the length of the tip of the aortic cannula.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results obtained in low-risk CABG are different from Hammon et al 23 who in higher-risk cases observed reduced rates of POCD with the modified single-clamp technique but no reduction in the HITS counts. Our findings are similar to those by Mullges et al 17 who did not find any effect on the rates of POCD due to the length of the tip of the aortic cannula.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies suggested neurocognition to be more related to aortic manipulation rather the use of extracorporeal circulation (30,31). The ROOBY trial demonstrated no difference in neurophysiological outcomes between off or on-pump groups (10).…”
Section: =0%) (1)mentioning
confidence: 99%
“…Finalmente, la ateromatosis aórtica no fue diferente entre los grupos con y sin DCPO. Si bien la ateroesclerosis es un factor de riesgo de accidentes vasculares cerebrales 44 , su relación con DCPO no es concluyente 45,[64][65][66] . Una de nuestras principales limitaciones es que las conclusiones sólo aplican a la totalidad de la población estudiada, sin permitir el análisis por subgrupos por falta de poder estadístico para ello.…”
Section: Discussionunclassified